2023
DOI: 10.3390/agronomy13020375
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Droplet Loss behind Canopies with Air-Assisted Sprayers Used for Fruit Trees

Abstract: Air-assisted sprayers are widely employed in orchards, but inappropriate spray parameters can lead to large droplet losses, pesticide waste, and environmental pollution. To investigate the factors affecting the droplet loss of an air-assisted sprayer behind canopies, a two-factor, five-level full experiment was conducted in an actual orchard, where the two factors were the power gradient and foliage area volume density (FAVD). In addition, the location of the sampling point was also considered in the data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The wind‐driven sprayers developed according to this technology rely on the formation of air‐assisted airflow along the nozzle direction; this can significantly improve the spray drift resistance and penetration and effectively offset or transform the ambient airflow's influence on the droplet movement state, reducing the pesticide contamination and increasing the efficiency 4–7 . Researchers in China and other countries have conducted numerous experiments on the influencing factors of spray drift and the drift loss process, aiming to reduce the spray drift amount and improve droplet spatial deposit by changing the air‐assisted airflow types and application parameters to clarify the spray drift prevention mechanism 8–11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wind‐driven sprayers developed according to this technology rely on the formation of air‐assisted airflow along the nozzle direction; this can significantly improve the spray drift resistance and penetration and effectively offset or transform the ambient airflow's influence on the droplet movement state, reducing the pesticide contamination and increasing the efficiency 4–7 . Researchers in China and other countries have conducted numerous experiments on the influencing factors of spray drift and the drift loss process, aiming to reduce the spray drift amount and improve droplet spatial deposit by changing the air‐assisted airflow types and application parameters to clarify the spray drift prevention mechanism 8–11 …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Researchers in China and other countries have conducted numerous experiments on the influencing factors of spray drift and the drift loss process, aiming to reduce the spray drift amount and improve droplet spatial deposit by changing the air-assisted airflow types and application parameters to clarify the spray drift prevention mechanism. [8][9][10][11] In anti-drift sprayers and droplet deposit characteristics, many studies have been conducted by both Chinese researchers and researchers from other countries. 12 For example, a study on the air-assisted flow and air-jet directions effect on droplet deposit found that increasing the air-assisted flow velocity effectively reduced drift.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the following three papers discuss and research improvements in automated agricultural equipment. Jiang et al [19] discussed issues related to significant droplet loss, pesticide wastage, and environmental pollution caused by improper spray parameters.…”
mentioning
confidence: 99%